THE GREAT PHENOMENON OF ONLINE SIRRI MARRIAGE FOR MALE AND FEMALE - Nasaiy Aziz (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2018)
Online sirri marriage is a marriage which is organized through skype or other social media without documentation from the marriage registration council. So far, the practice of online sirri marriage in Indonesia is very apprehensive and to be serious problem in the society. It happened because the regulation that control marriage which is stated in law (UU) of marriage and compilation of Islamic law tend to be ignored. The requirement of the guardian (Wali) as regulated by Islamic law is ignored. However, the online sirri marriage is organized by involving marriage celebrant (penghulu) as magistrate guardian (wali hakim) who married off which is not detected by the woman's parents, her guardian, and marriage registrar. The practice of online siri marriage is performed by using skype media and other social media that the face of penghulu and the two brides can be seen directly. The consequences that will arise are uncertainty of law and law protection, especially for women and children who could not claim their rights when family conflict occurred. This kind of marriage is legal (sah) when it is implemented in accordance with the rules and prerequisites in Islamic law. However, the phenomenon of sirri marriage which is performed arbitrarily contradicts the Islamic law, because the completeness one of the pillars of marriage that is involvement of guardians is not fulfilled as well as many mafsadah occurs. In addition, online sirri marriage is also not recognized by the state, because it could not be proven by the marriage certificate.